2003
DOI: 10.1002/ls.3010150203
|View full text |Cite
|
Sign up to set email alerts
|

Friction‐induced two‐dimensional solid films from lubricant additives

Abstract: Tribochemical interactions between some lubricant additives, namely zinc dithiophosphate (ZnDTP), an antiwear additive, molybdenum dithiocarbamate (MoDTC), a friction modifier, and overbased calcium borate (OCaB) detergent, have been investigated. The nature of the tribofilms formed was studied by combining high‐resolution transmission electron microscopy of wear fragments and inside wear scars with micro‐spot X‐ray photoelectron spectroscopy at the same location of the wear track (‘dual’ analysis). The OCaB/Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Thus, the easy sliding of the MoS 2 sheets could result from a favourable orientation induced by sufficiently high contact pressure values. The ability of MoS 2 sheets to orient in a favourable direction was reported by Grossiord et al [31] and Martin et al [32], who recently investigated tribochemical interactions between ZDTP, MoDTC and OCB (overbased detergent calcium borate) additives. Using high resolution TEM observations of wear debris, coupled with wear scar micro-spot XPS analysis, they observed perfectly oriented MoS 2 sheets, with their basal plane parallel to the flaky wear fragments.…”
Section: Discussionmentioning
confidence: 70%
“…Thus, the easy sliding of the MoS 2 sheets could result from a favourable orientation induced by sufficiently high contact pressure values. The ability of MoS 2 sheets to orient in a favourable direction was reported by Grossiord et al [31] and Martin et al [32], who recently investigated tribochemical interactions between ZDTP, MoDTC and OCB (overbased detergent calcium borate) additives. Using high resolution TEM observations of wear debris, coupled with wear scar micro-spot XPS analysis, they observed perfectly oriented MoS 2 sheets, with their basal plane parallel to the flaky wear fragments.…”
Section: Discussionmentioning
confidence: 70%
“…These two studies probe the material at the atomic level providing useful information for the study of exfoliation of graphene like materials. Ex situ studies on MoS 2 tend to suggest the validity of these studies, as crystallites have been observed to become oriented by the shear forces experienced in tribological wear. , Doping of MoS 2 with other transition metals is also of interest and is known to increase the wear resistance of the material without dramatic loss of superlubricity . The effect this transition metal inclusion has on the mechanical failure mode of MoS 2 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the MoDTC additive reduces friction by forming a tribofilm containing MoS 2 , which lowers the shear strength of the tribofilm, while the ZDDP additive plays a role in enhancing wear resistance and promoting the formation of MoS 2 [12,[18][19][20]. In the case of molybdenum dithiocarbamate, the high-resolution electron microscopy (HRTEM) study performed on wear fragments have shown that MoS 2 is formed in the contact by decomposition of the additive molecule [21,22].…”
Section: Discussionmentioning
confidence: 99%